2014
DOI: 10.1089/cbr.2014.1622
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-3P-RGD2 Micro-Single-Photon Emission Computed Tomography/Computed Tomography Provides a Rational Basis for Integrin αvβ3-Targeted Therapy

Abstract: Purpose: This study was to demonstrate the utility of 99m Tc-3P-RGD 2 micro-single-photon emission computed tomography/computed tomography (SPECT/CT) for the integrin a v b 3 expression quantification in NCI-H446 and A549 lung cancer xenografts. Materials and Methods: 99m Tc-3P-RGD 2 was prepared with high radiochemical purity (97% -2%) and showing high in vitro stability. The in vitro affinities of 99m Tc-3P-RGD 2 to NCI-H446 and A549 tumor cells were analyzed with c-counter, while the in vivo uptakes in NCI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…99m Tc-3PRGD2 radiotracer was prepared as described previously. [ 18 ] Briefly, the kit contained 20 μg hydrazinonicotinamide-3PRGD2, 5 mg trisodium triphenylphosphine-3,3′,3′′-trisulfonate, 6.5 mg tricine, 40 mg mannitol, 38.5 mg disodium succinate hexahydrate, and 12.7 mg succinic acid. For 99m Tc radio labeling, 1.0 mL of 1110 to 1480 MBq (30–40 mCi) of Na 99m TcO 4 solution was added to a lyophilized vial.…”
Section: Methodsmentioning
confidence: 99%
“…99m Tc-3PRGD2 radiotracer was prepared as described previously. [ 18 ] Briefly, the kit contained 20 μg hydrazinonicotinamide-3PRGD2, 5 mg trisodium triphenylphosphine-3,3′,3′′-trisulfonate, 6.5 mg tricine, 40 mg mannitol, 38.5 mg disodium succinate hexahydrate, and 12.7 mg succinic acid. For 99m Tc radio labeling, 1.0 mL of 1110 to 1480 MBq (30–40 mCi) of Na 99m TcO 4 solution was added to a lyophilized vial.…”
Section: Methodsmentioning
confidence: 99%
“…Radiolabelled RGD peptide as a target ligand for angiogenesis imaging has been well documented in preclinical and clinical studies [18,26,27]. In a previous multicentre study, we showed that Tc-labelled RGD dimers, such as 99m Tc-3PRGD 2 , had high sensitivity for the detection of lung cancer, including primary and metastatic tumours [26,28,29]. 99m Tc-Galacto-RGD 2 , with higher a nity to α v β 3 and a favourable biodistribution, has been synthesized and utilized for the quantitative evaluation of α v β 3 expression and of tumour angiogenesis, which may in turn serve as a prognostic hallmark and may aid treatment strategy selection [30].…”
Section: Introductionmentioning
confidence: 90%
“…Radiolabelled RGD peptide as a target ligand for angiogenesis imaging has been well documented in preclinical and clinical studies [ 12 , 21 , 22 ]. In a previous multicentre study, we showed that [ 99m Tc]Tc labelled RGD dimers, such as [ 99m Tc]Tc-3PRGD 2 , had high sensitivity for the detection of lung cancer, including primary and metastatic tumours [ 21 , 23 , 24 ] . [ 99m Tc]Tc-Galacto-RGD 2 , with higher affinity to α v β 3 and a favourable biodistribution, has been synthesized and utilized for the quantitative evaluation of α v β 3 expression and of tumour angiogenesis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%